Climate Change in Wales and its health impact: Who is vulnerable and how?. (20th October 2021) - Green, L; Edmonds, N
Abstract: In April 2019, Wales declared a climate emergency. Public Health Wales commissioned a Health Impact Assessment (HIA) to be carried out to assess the potential impact of Climate Change (CCh) on the population of Wales and inform key strategic decision makers to understand/plan for the potential differential health and inequalities impacts that may occur from CCh. A comprehensive mixed-method HIA was conducted over a 6 month period in 2019/2020. A review of peer-reviewed evidence on the potential impact of CCh/climate change events on health and population groups and a review of grey literature on direct impacts such as the environment, mental wellbeing and health care settings was conducted. 2 stakeholder workshops, qualitative interviews, a community health profile utilising sources such as the National Survey for Wales were also carried out. All findings were analysed, synthesized and collated into a report. Vulnerability is a critical aspect of population health and the HIA findings identified a range of positive and negative impacts on specific population groups which highlights their vulnerability to climate change. This includes children and young people; older people; coastal and rural communities and those on low incomes. These are often not explicitly highlighted in other environmentally focused assessments. The HIA also indicated significant potential impacts across the determinants of health including excess heat/cold; flooding; economy; access to services; mental well-being; and community resilience. The findings have informed decision-makers to prepare for CCh plans/policies using an evidence-informed approach and particularly to address who may be disproportionately negatively affected. The work has demonstrated the importance of HIA to assess significant, complex policies by mobilising a range of evidence through a transparent process, explicitly considering the impact on vulnerable groups, resulting in transferrable learning for others.